Production of indigenous alcoholic beverages in a rural village of Cameroon. Issue 2 (13th January 2014) - Kubo, Ryosuke; Funakawa, Shinya; Araki, Shigeru; Kitabatake, Naofumi
<x xml:space="preserve">Abstract</x> In this study, the indigenous alcoholic beverages in a rural village of Cameroon were investigated. The technique for producing alcoholic beverages in the village was observed, and the concentrations of ethanol, glucose and lactic acid and the pH values during the course of production were measured using portable devices at the field site. Eight different kinds of alcoholic beverage (palm wine, palm spirits, raffia wine, cassava spirits, maize turbid beer, maize spirits, plantain wine and plantain spirits) were produced and consumed in the village. Of these beverages, palm wine, made from palm sap, was the most important alcoholic beverage in a villager's daily life. In addition, starch‐based alcoholic beverages were distilled rather than drunk directly. As germinated maize, which has a relatively low amylase activity, was used as an amylase source in production, starch‐based alcoholic beverages might need to be distilled to enhance the ethanol concentration. During the course of production, the pH was reduced using local techniques, which proved to be effective in preventing bacterial contamination. Copyright © 2014 The Institute of Brewing & Distilling